A study of tensile and bending properties of 3D-printed biocompatible materials used in dental appliances - García Reyes, Marcos; Bataller-Torras, Alex; Cabrera-Carrillo, Juan Antonio; Velasco García, Juan María; Castillo-Aguilar, Juan Jesús (Springer, 2022)
In the last years, a large number of new biocompatible materials for 3D printers have emerged. Due to their recent appearance and rapid growth, there is little information about their mechanical properties. The design and manufacturing of oral appliances made with 3D printing technologies require knowledge of the mechanical properties of the biocompatible material used to achieve optimal performance for each application. This paper focuses on analyzing the mechanical behaviour of a wide range of biocompatible materials using different additive manufacturing technologies. To this end, tensile and bending tests on different types of recent biocompatible materials used with 3D printers were conducted to evaluate the influence of the material, 3D printing technology, and printing orientation on the fragile/ductile behaviour of the manufactured devices. A test bench was used to perform tensile tests according to ASTM D638 and bending tests according to ISO 178. The specimens were manufactured with nine different materials and five manufacturing technologies. Furthermore, specimens were created with different printing technologies, biocompatible materials, and printing orientations. The maximum allowable stress, rupture stress, flexural modulus, and deformation in each of the tested specimens were recorded. Results suggest that specimens manufactured with Stereolithography (SLA) and milling (polymethyl methacrylate PMMA) achieved high maximum allowable and rupture stress values. It was also observed that Polyjet printing and Selective Laser Sintering (SLS) technologies led to load-displacement curves with low maximum stress and high deformation values. Specimens manufactured with Digital Light Processing (DLP) technology showed intermediate and homogeneous performance. Finally, it was observed that the printing direction significantly influences the mechanical properties of the manufactured specimens in some cases.
Keywords: Materiales biomédicos; Implantes dentales; 3D printing; Material Properties; Biocompatible; Dental Appliances